Design Principles of Current Collectors in Microfluidic Fuel Cell with Flow-through Porous Electrodes. (May 2017) - Li, Li; Fan, Wenguang; Xuan, Jin; Leung, Michael K.H.; Zheng, Keqing; She, Yiyi
Abstract: Computational and experimental studies have been performed to investigate the effects of current collector design on the performance of microfluidic fuel cell (MFC) with flow-through porous electrodes. Characteristics of electron transport in MFC with flow-through porous electrodes are investigated based on a three-dimensional computational model. The lateral electron transport in the porous electrode is found to encounter high resistance. To improve the cell performance, influences of different current collector design parameters on the transport resistances are examined. Physical origins for the influences of different design parameters are also discussed. The results demonstrate that current collector position is the most influential factor due to the non-uniform flow rate distribution. In the experimental study, cell performances revealed maximum power density when current collectors were located at the high flow rate region. An increase of 61% was observed when the current collectors moved from the conventional exposed ends of the electrodes to the high flow rate regions in the electrode active area. Based on the results, some general rules are set for the current collector designs of MFCs.